2009
DOI: 10.1074/jbc.m109.019521
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Condensation of Copper with Elevated β-Amyloid in Lipid Rafts under Cellular Copper Deficiency Conditions

Abstract: Redox-active copper is implicated in the pathogenesis of Alzheimer disease (AD), ␤-amyloid peptide (A␤) aggregation, and amyloid formation. A␤⅐copper complexes have been identified in AD and catalytically oxidize cholesterol and lipid to generate H 2 O 2 and lipid peroxides. The site and mechanism of this abnormality is not known. Growing evidence suggests that amyloidogenic processing of the ␤-amyloid precursor protein (APP) occurs in lipid rafts, membrane microdomains enriched in cholesterol. ␤-and ␥-secreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 70 publications
(58 reference statements)
3
76
0
Order By: Relevance
“…Previous findings showed that copper increases APP cell surface localization (58) and promotes APP trafficking from the Golgi to intracellular compartments and to the cell surface (32). This supports H147N-APP decreased post-Golgi trafficking because His 147 might be necessary for APP copper binding.…”
Section: Discussionsupporting
confidence: 59%
“…Previous findings showed that copper increases APP cell surface localization (58) and promotes APP trafficking from the Golgi to intracellular compartments and to the cell surface (32). This supports H147N-APP decreased post-Golgi trafficking because His 147 might be necessary for APP copper binding.…”
Section: Discussionsupporting
confidence: 59%
“…It has been reported that exposure to copper decreases A␤ levels (31,32,39,71,72). Under conditions used in this study, we did not observe any detectable changes in APP processing.…”
Section: Discussionmentioning
confidence: 34%
“…Copper-stimulated Relocalization of APP in Cultured Neuronal and Polarized Epithelial Cells-We previously reported that in the human neuroblastoma SH-SY5Y cell line, an increase in copper concentration stimulated an increase in the level of APP at the cell surface (39). In the present study, we further investigated the influence of copper on APP trafficking in both neuronal and polarized epithelial cell models using confocal fluorescence imaging techniques.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations